Synaptic transmission in supragranular layers of the human cortex – comparative review of structure, function, and plasticity - Eichler, Amelie; Kruse, Pia; Schob, Charlotte; Lenz, Maximilian (Frontiers in Synaptic Neuroscience, 2025)
Synapses are the highly specialized connection sites between neurons enabling the establishment of complex neuronal networks. As highly plastic structures, synapses collocate both the transmission and storage of information, which is an essential prerequisite for learning and memory. Since synaptic deficits are associated with degenerative and neuropsychiatric diseases, it is essential to understand the mechanisms of synaptic plasticity. Throughout evolution, the human brain has developed distinct characteristics, such as supragranular expansion and enhanced long-range connectivity, suggesting an evolutionary specialization of synapses. Recent collaborative research, employing slice preparations obtained from neurosurgical resections of the human neocortex, has significantly advanced our understanding of the unique structural and functional properties of the human neocortex. This review investigates findings derived from diverse experimental methodologies, highlighting specific synaptic features. Focusing on synapses in supragranular layers, we discuss the distinctive synaptic structure, function, and mechanisms of plasticity that contribute to the unique circuitry of the adult human brain. Additionally, we outline emerging directions of research aimed at further elucidating the functionality of human cortical networks.